Developing Patient-Centered Real-World Evidence: Emerging Methods Recommendations From a Consensus Process - Oehrlein, Elisabeth M.; Schoch, Silke; Burcu, Mehmet; McBeth, Julia F.; Bright, Jennifer; Pashos, Chris L.; Willke, Richard; Love, T. Rosie; Mattingly, T. Joseph; Perfetto, Eleanor M. (Value in health, 2023)
The Joint ISPOR-ISPE Special Task Force on Real-World Evidence included patient/stakeholder engagement as a recommended good procedural practice when designing, conducting, and disseminating real-world evidence (RWE). However, there are no guidelines describing how patient experience data (PED) can be applied when designing real-world data (RWD) studies. This article describes development of consensus recommendations to guide researchers in applying PED to develop patient-centered RWE. A multidisciplinary advisory board, identified through recommendations of collaborators, was established to guide development of recommendations. Semistructured interviews were conducted to identify how experienced RWD researchers (n = 15) would apply PED when designing a hypothetical RWD study. Transcripts were analyzed and emerging themes developed into preliminary methods recommendations. An eDelphi survey (n = 26) was conducted to refine/develop consensus on the draft recommendations. We identified 13 recommendations for incorporating PED throughout the design, conduct, and translation of RWE. The recommendations encompass themes related to the development of a patient-centered research question, designing a study, disseminating RWE, and general considerations. For example, consider how patient input can inform population/subgroups, comparators, and study period. Researchers can leverage existing information describing PED and may be able to apply those insights to studies relying on traditional RWD sources and/or patient registries. Applying these emerging recommendations may improve the patient centricity of RWE through improved relevance of RWE to patient communities of interest and foster greater multidisciplinary participation and transparency in RWD research. As researchers gather experience by applying the methods recommendations, further refinement of these consensus recommendations may lead to “best practices.”